The Influence of the Shariah Supervision Board on Corporate Social Responsibility Disclosure by Islamic Banks of Gulf Co-Operation Council Countries - Abdul Raman, Azhar; Bukair, Abdullah Awadh (Asian Journal of Business and Accounting, 2013)
This paper examines empirically the influence of the Shariah supervisory board (SSB) and its characteristics on the level of corporate social responsibility (CSR) disclosure in a sample of 53 Islamic banks operating in Gulf Co-operation Council (GCC) countries for the year 2008 based on a disclosure index from the Islamic perspective. Using content analysis, the descriptive statistics show that there is an increase in CSR information disclosed in the annual reports of Islamic banks. In addition, using multiple regression analysis and after accounting for bank size, financial performance and economic performance, the findings indicate that the combination of SSB attributes has a significant positive influence on CSR disclosure. This means that the characteristics of SSB are important factors in determining the level of CSR disclosure. Keywords: Islamic Banks, Shariah Supervision Board, Corporate Social Responsibility, Disclosure JEL Classification: G21, M14, M41, Z12